Letters - Schoenberg, Arnold 1874-1951; Stein, Erwin (London Faber and Faber, 1987)
Background notes about each stage of his life and career, accompany Schoenberg's letters to artists, intellectuals, and fellow composers.
Keywords: 20th Century (1901-2000); Composer; Correspondence